Remote laboratory access and network simulation tools for students with vision impairment - Murray, Iain; Armstrong, Helen (IARIA, 2009)
The delivery of laboratory exercises to students that are unable to attend in person due to physical disabilities is a significant issue. Both Netlab and Packet Tracer are inaccessible to many students who use assistive technology, particularly those with vision impairment. This paper presents the development of an accessible, cost effective, remote laboratory and describes the modification to laboratory sessions necessary for the blind to undertake Cisco Certified Network Associate (CCNA) laboratory sessions remotely and with full accessibility. Also discussed is the development of an accessible network simulator, iNetSim, illustrating possible methodologies that may be applied to make existing simulation packages accessible to those with severe vision impairment.